TOXICITY OF HYDNORA JOHANNIS BECCARI (HYDNORACEAE) DRIED ROOTS AND ETHANOL EXTRACT IN RATS - Yagi, S.; Adam, S.; Chapleur, Y.; Laurain-Mattar, D. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Roots of Hydnora johannis are used for the treatment of dysentery, diarrhea, cholera, and tonsillitis in Sudan [1]. The high tannin content of the roots may explain the relief provided for the condition due to the astringent and anti-inflammatory effects [2]. The aim of the present work was to evaluate the toxic effects of dried roots and of the ethanol extract of Hydnora johannis. Wistar rats were divided into 4 groups: rats in group 1 were controls, group 2 were given increasing concentration of dried roots ad lib in diet; group 3 were given increasing concentrations of ethanol extract orally; group 4 were given ethanol extract intramuscularly. Histopathological analysis as well as haematological and biochemical tests were carried out. The analysis showed a dose-dependant effect, mainly on the liver and spleen, in the three groups. However, the impact of the dried roots was very mild compared to that of the ethanol extract. Moreover, intramuscular administration of ethanol extract incurred more damage than the oral root treatment. Thus, the difference in the toxic effect in this experiment might be due to the route of administration as well as the extraction method. The amount of tannins could be higher in the ethanol extract whereas dried powder in the diet may yield less of the hydrolysable tannins in addition to the astringent effect of tannins which decrease the rate of absorption.